Downregulating Serine Hydroxymethyltransferase 2 Deteriorates Hepatic Ischemia-Reperfusion Injury through ROS/JNK/P53 Signaling in Mice. (18th November 2019) - Wu, Hao; Bai, He; Duan, Shigang; Yuan, Fangchao
Abstract : Background . Serine hydroxymethyltransferase 2 (SHMT2) activity ensures that cells have a survival advantage in ischemic conditions and regulates redox homeostasis. In this study, we aimed to investigate the role of SHMT2 after hepatic ischemia-reperfusion (IR), which involves hypoxia, ischemic conditions, and cell apoptosis. Methods . A 70% IR model was established in C57BL/6J mice with or without SHMT2 knockdown. H&E staining, liver weight/body weight, serum alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels and cell apoptosis were tested to analyze liver damage and function. Then, the related cellular signals were probed. Results . The level of SHMT2 protein was significantly increased at 24 h and 48 h after IR (p < 0.001 ). Mice in the shSHMT2 group showed more necrotic areas and histological damage at 24 h (p < 0.01 ) after IR and higher levels of serum ALT and AST (p < 0.05 ) compared with those of mice in the scramble group. After IR for 24 h, the expression of TUNEL in the shSHMT2 group was significantly higher than that in the scramble group, as shown by histological analysis (p < 0.01 ). Mechanistically, the JNK/P53 signaling pathway was activated by IR, and knockdown of SHMT2 exacerbated hepatocyte apoptosis. Conclusions . Knockdown of SHMT2 worsens IR injury through the ROS/JNK/P53 signaling pathway. Our discovery expands the understanding of both molecular and metabolic mechanisms involved in IR. SHMT2 is a possible therapeutic target to improve the prognosis of liver transplantation (LT) and subtotal hepatectomy.